Źródła finansowania inwestycji gmin polskich w latach 1999-2003 - Godoń-Więznowska, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The author in the article describes and comments sources of funds used for investment in polish communes during the years 1999-2003. First the investment as a tool for realisation of communes' goals is defined and explained. Then the author analyses in detail the internal sources of founds of polish communes. The other ways to finance investment used by communes in Poland are researched in the last part of the article.Author stresses the decrease in share of internal financial sources what increases the dependence of communes of government administration. And these internal sources were the most important reservoir of funds available for investment in researched period. Big importance of internal financial sources is caused by difficulties in rising other funds - i.e. credits, subventions and other transfers.The decrease of income of communes in 2003 caused substantial decrease in investment, what gave a shock to communal finances and slowed the growth of researched entities. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 565-577